Cutaneous Side Effects of Targeted Therapy and Immunotherapy for Advanced Melanoma. (30th December 2018) - Russo, Irene; Zorzetto, Ludovica; Chiarion Sileni, Vanna; Alaibac, Mauro
Abstract : Melanoma is one of the most fatal cancers, and its incidence is increasing worldwide. Thanks to the better understanding of the molecular mechanisms involved in the pathogenesis of melanoma, recently new targeted agents have been developed. In this article, we review the current state of knowledge of clinical presentation, mechanisms, and management of the most common cutaneous side effects observed during treatment with targeted and immunological therapies approved for advanced melanoma. We include discussion of BRAF/MEK inhibitors and immune-checkpoint inhibitors, notably CTLA-4 and PD-1 inhibitors.